SMEs Performance Based on Strategic Leadership: The Role Mediating of Dynamic Capabilities - Engga, Engga Jalaludin; Sobandi, A.; Santoso, Budi (Eastasouth Institute, 2024)
This study aims to bridge the gap from some previous research results that examine the correlation between strategic leadership and firm field-presentation by using the dynamic capability model (staff empowerment with flexible and integrated capability, resilient dynamic capability and agility dynamic capability) as a go-between variable. This study examines the direct outcome of strategic leadership on SME field-presentation and then examines the indirect effect through the in-between role of dynamic capability (staff empowerment with flexible and integrated capability, resilient dynamic capability and agility dynamic capability) on SME performance. The method utilized in this study is statistical analysis method by conducting an online survey to SME owners/managers in Jakarta. From the survey distributed, a total of 475 respondents returned the questionnaire that had been answered and valid. The collected data were analyzed using SEM-PLS 4.0. The results showed that strategic leadership variables have a positive and significant influence on SME performance. Similarly, the same results are shown in the indirect results of strategic leadership variables on SME performance through the afro mentioned go-between role of dynamic capability (staff empowerment with flexible and integrated capability, potent dynamic capability and agility dynamic capability).